Integrasi Ilmu Agama Dalam Sistem Pendidikan di Era Pasca Keruntuhan Kekhalifahan Islam - La Denna Hasri Monasari; Indah Winarni; Muhammad Fariz; Herdi Tri Nanda; Nurjanah Nurjanah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Education and knowledge are essential for effectively integrating different fields of study. The combination of religious-based lessons with general lessons in the modern era is particularly important, especially in Islamic education. To achieve this, strong educational institutions are needed that can accommodate these fields of knowledge. The integration of science and religion into Islamic education can be achieved through various means. This includes incorporating science and religion into the curriculum, the teaching and learning process, and social education aspects. Therefore, high-quality educational institutions can blend religion and science to meet the needs of their students, rather than applying a dichotomy of knowledge.